PENGANTAR ILMU HUKUM - Ikhsan , Muhammad; Wahid, St. Hadijah (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
This article discusses the basics of legal science, which includes the concepts, sources and legal systems that apply in Indonesia, as well as the challenges and opportunities in facing the development of globalization and digitalization. The research method used is a qualitative approach with analysis of the latest literature in the last five years. The findings of this research reveal that law is not just a set of written rules, but also reflects dynamic social values and norms. In the Indonesian context, law is influenced by pluralism involving customary law, Islamic law and Western law, creating its own challenges in harmonization of regulations. Apart from that, globalization and digitalization have brought significant changes in various aspects of life, including law. Increasing digital transactions, personal data protection, and developments in information technology demand regulatory updates that are more adaptive and responsive. This study shows that the Indonesian legal system must be able to transform and adopt innovative approaches to address these contemporary issues.